Analysis of Potential Factors on Contract Change Order (CCO) and Quality Performance and Design of Sicco Innovations in Road Infrastructure Projects in Tangerang - Zulkifli Faizal; Muhammad Isradi (Eduvest - Journal of Universal Studies, 2026)
This study examines the factors influencing Contract Change Orders (CCO) and their relationship with quality performance in road infrastructure projects in Tangerang Regency. Based on DBMSDA data from 2022 to 2024, there were notable changes in contract values, especially in projects exceeding 1 billion IDR. The findings reveal that policy changes, specification adjustments, and planning errors are key contributors to CCO occurrences. Using SmartPLS 4.0 and the Structural Equation Modeling (SEM) method, the research analyzes the interrelationships between variables and their impact on project quality performance. The results demonstrate that effective coordination and strong planning significantly improve quality outcomes, while the scope of CCO directly influences overall project results. To support better governance, the study also proposes the development of a digital application for managing CCO submissions to enhance efficiency, transparency, and monitoring within the approval process. Overall, this research provides useful insights for stakeholders in infrastructure development to optimize project implementation, minimize risks, and improve quality performance in road construction projects.